THE EFFECT OF THE READING, QUESTIONING AND ANSWERING LEARNING MODEL ON STUDENTS' ACCELERATION ANALYSIS ABILITY IN FLUID MECHANICS PHYSICS EDUCATION 2021 - Az Zahra Lintang Kinanti; Yushardi (Journal of Learning and Technology in Physics, 2025)
This study aims to determine and analyze the improvement in the use of the RQA learning model on the ability to analyze gravitational acceleration in Fluid Mechanics material. This type of research is a quasi-experimental study with the population in this study being Physics Education students of the University of Jember class of 2021. Sampling used cluster random sampling by randomly selecting class A as the experimental class and class B as the control class. The instruments used were a learning outcome test in the form of an essay of 5 questions and independent practicum. The average value of student learning outcomes treated with the RQA learning model was 71.97 and 64.80 for the learning model in general. Based on the results of the t-test calculation analysis using IBM SPSS Statistics version 25, there is a significant effect of the application of the RQA learning model on the analytical abilities of physics education students' 21. Keywords: RQA learning model, analytical skills, gravitational acceleration, fluid mechanics